2015
DOI: 10.12738/estp.2015.6.0102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calibration Sample Size and Item Bank Size on Ability Estimation in Computerized Adaptive Testing

Abstract: This study aimed to investigate the effects of calibration sample size and item bank size on examinee ability estimation in computerized adaptive testing (CAT). For this purpose, a 500-item bank pre-calibrated using the three-parameter logistic model with 10,000 examinees was simulated. Calibration samples of varying sizes (150,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Furthermore, in some cases the complexity associated with administering and scoring an adaptive test may not be warranted given similar performance can be achieved through the use of a static short form comparator test (Reise & Henson, 2000). Indeed, studies have shown that the efficiency and precision associated with different CATs can vary depending on the quality of the item bank and the number of items that target specific severity levels on the latent traits (Şahin & Weiss, 2015). The current study aimed to determine the efficiency versus precision of an adaptive test based on multidimensional IRT through the use of computer simulations.…”
Section: The Current Studymentioning
confidence: 99%
“…Furthermore, in some cases the complexity associated with administering and scoring an adaptive test may not be warranted given similar performance can be achieved through the use of a static short form comparator test (Reise & Henson, 2000). Indeed, studies have shown that the efficiency and precision associated with different CATs can vary depending on the quality of the item bank and the number of items that target specific severity levels on the latent traits (Şahin & Weiss, 2015). The current study aimed to determine the efficiency versus precision of an adaptive test based on multidimensional IRT through the use of computer simulations.…”
Section: The Current Studymentioning
confidence: 99%
“…Furthermore, CATs with a relatively smaller number of items in their item banks have been shown to function suitably. Sahin and Weiss (2015) have demonstrated that small item banks can still lead to accurate item parameter and ability estimates in CAT using simulated data with items having sufficient information. In another study conducted on a language test using real data, CATs with as few as 20 items were shown to produce promising results with SE values of 0.35 (Kaya & Kalender, 2018).…”
Section: Instrumentmentioning
confidence: 99%
“…Within each interval, 25 realizations of a uniform distribution with the corresponding bounds were generated (Finkelman et al, 2010). The c parameters were realizations of a U[0.00, 0.25] distribution (Sahin & Weiss, 2015). In this EF item bank consisting of the 300 true (i.e., not estimated) item parameters, the means and standard deviations for the a, b, and c parameters were 1.21 (0.40), 0.00 (1.73), and 0.12 (0.07), respectively.…”
Section: Simulationmentioning
confidence: 99%